Hypothetical Purchase Task Questionnaires for Behavioral Economic Assessments of Value and Motivation. (18th May 2015) - Roma, Peter G.; Hursh, Steven R.; Hudja, Stanton
Abstract : We tested effects of hypothetical purchase task (HPT) questionnaire price density (17, 9, or 5 prices) and purchase type (quantity purchased or probability of single purchase) on behavioral economic (BE) measures of value for six commodities. The exponential model of demand provided excellent fits for all HPTs (mean R 2 = 0.98). High density HPTs were most sensitive yet most resistant to distortion. BE value measures were lower in quantity versus probability HPTs. Rank ordering of commodity values agreed regardless of HPT structural manipulations. Expenditure curves were unexpectedly bimodal, but consistent with exponential model predictions. Implications for HPT construction and BE research are discussed. Copyright © 2015 John Wiley & Sons, Ltd.